PENGARUH PENAMBAHAN EFFECTIVE MICROORGANISM-4 (EM-4) PADA PENGOMPOSAN TERHADAP PRODUKSI JAMUR MERANG - Yuliastrin, Adisti (Jurnal Matematika Sains dan Teknologi, 2007)
This research was aimed for knowing the influence of  EM-4 (effective microorganism-4) addition and the most effective concentration of EM-4 in compost media for straw mushroom (Volvariella volvacea (Bull. ex Fr.) Sing) production. The treatment examined the use of EM-4 solution divided into six treatments and four repetitions. EM-4 concentration from 0 ml/l – 12,5 ml/l with an interval increasing of 2,5 ml/l. The addition of 7,5 ml/l – 12,5 ml/l concentration of EM-4 did not give so different result with the control media. Composting with addition of 5 ml/l EM-4 gave the highest straw mushroom production (2272,25 g). Statistically the result showed that the concentrations of EM-4 had no significant effect on the mushroom production.